KELAM`DA AKLIN KONUMU VE SINIRI - YAZICI, SEMRA (Fırat Üniveristesi, 2007)
Yüce Allah, Kur'an'da insanın düşünce yeteneğine aklına dikkat çekerek,aklını kullanmasını istemektedir. Kur'an insanın hem dünyada hem de ahirettehuzurlu ve mutlu olabilmesi için, insanın aklını kullanmasını ısrarla istemektedir.İnsanı diğer canlılardan yarına en önemli vasıf akıldır. İslam'da dinen mü-kellef olmak için aklı öncelikli şart koşmuştur. Kur'an'da akıl kelimesi birçokyerde kullanılmıştır. Ayetlerde ?akletmemiz?, aklı kullanarak doğru düşünmeninüzerinde durulmuştur.Akıl ve işlevleri ne kadar önemli ise de sadece akıl kendi başına bilgiedinmemizde yeterli değildir. Akıl belli bir saha içinde düşünülebilir. Yani akılbazı şeyleri kavramada sınırlıdır; bazı şeyleri bilmeyebilir. Bizi yaratan, insanlığıen iyi şekilde bildiği için eksik olan insanın bu özelliğini, vahiyle tamamlamıştır.Anahtar Kelimeler; akıl, düşünmek, bilgi, sınır.

By attracting attention to the people?s thought ability in the Quran Godwants human being to use their intelligence. The Quran demands people to usetheir wisdom insistently so as to be happy and in peace both in this world and thenext one.A comprehension is the most important attribute which separates humanbeing from the other creatures. In order to be charged in the religion. Islam laysdown wisdom as a condition. The word intelligence has been used in a lot ofplaces. In the Quranic verses the word refers to think reasonably by using mem-ory.Although intelligence and its function are important. Though is not enoughonly to gain information. Reason can be used only in a restricted field. That meansit is limited to comprehend some things. It may not know some things. As godknows the human being very well, he has completed this de efficiency of the peo-ple by sending divine inspiration.Key words: wisdom, to think, knowledge, limit.
The location of the intelligence and its limit in Islamic theology
Keywords: Din